Volumetric Nanoscale Imaging: Hard X‐Ray Nanoholotomography: Large‐Scale, Label‐Free, 3D Neuroimaging beyond Optical Limit (Adv. Sci. 6/2018). Issue 6 (19th June 2018) - Khimchenko, Anna; Bikis, Christos; Pacureanu, Alexandra; Hieber, Simone E.; Thalmann, Peter; Deyhle, Hans; Schweighauser, Gabriel; Hench, Jürgen; Frank, Stephan; Müller‐Gerbl, Magdalena; Schulz, Georg; Cloetens, Peter; et al.
Abstract : In article number1700694, Bert Müller and co‐workers launch nano‐holotomography for the isotropic 3D imaging of paraffin‐embedded human brain tissues. Nano‐holotomography bridges the spatial resolution gap between optical and electron microscopy, while giving access to 3D data for large tissue volumes with a spatial resolution well below 100 nm. The hierarchical approach will mediate prospering nano‐anatomy.